Desenvolvimento e caracterização de filmes poliméricos contendo extrato de cascas de frutos de Punica granatum para uso como cobertura bioativa na farmacoterapia veterinária - Costa, Nubya Nascimento (2021)
As well as the search for bioactive compounds from medicinal plants with healing activity, the development of new pharmaceutical dosage forms to convey them is a growing demand. In this context, the present work aimed to produce polymeric films based on blends between poly(vinyl alcohol) (PVA), corn starch and poly (acrylic acid) (PAA), containing total dry extract of Punica granatum (pomegranate) peels (ESTCR), to use as bioactive wound dressing in veterinary pharmacotherapy. The work was carried out in two stages. In the first phase, the minimum inhibitory concentration of ESTCR on Gram-positive and Gram-negative bacteria strains and a fungus and, the best concentration of the extract in films prepared by solvent casting with different proportions of polymers were defined. The films were characterized by thermal analysis (DSC and TG/DTG) and their barrier properties were evaluated. Furthermore, biocompatibility and healing activity were preliminarily evaluated using in vitro techniques. From the data analysis, the best formuation was chosen, prepared from polymers in the 75:15:10 ratio (PVA/starch/PAA) and in the presence of 1.25% w/w of the extract. In the second phase, the best formulation was submitted to complementary tests of physicochemical characterization: scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD); tensile tests to investigate mechanical properties; and, to disc diffusion tests, to evaluate the antifungal activity. Were obtained smooth, transparent, bright, light yellow films, without the presence of domains when evaluated visually. The different proportions of polymers in the formulations caused changes in the studied characteristics of the films. The PVA:S:PAA:PPE4 produced a smooth, transparent film, free of domination and without phase separation. Furthermore, the film showed barrier properties appropriate for use as a bioactive wound dressing. When submitted to the in vitro hemolytic activity assay, the film proved to be non-hemolytic and biocompatible. In addition to the antibacterial activity on the strains studied, the films were efficient in promoting cell proliferation in vitro, within 48 h, without cytotoxicity. Complementary analysis in the chosen film (PVA:S:PAA:PPE4) proved the existence of interactions between the extract components and the polymers, contributing to the formation of uniform, handling-resistant films with mechanical properties necessary for use as bioactive covers. Analysis of the photomicrographs of the fractured surfaces point to the presence of discontinuities in the matrix, justifying the small reduction observed in the parameters of mechanical resistance when compared to the values for the film without extract. The change in the organization of polymer chains was also confirmed by XRD. Finally, films with extract showed antifungal activity on the studied Candida albicans strain. The analysis of all results allows us to infer that the film PVA:S:PAA:PPE4, prepared from polymers in the proportion 75:15:10 (PVA:starch:PAA) containing ESTCR at a concentration of 1.25% w/w is potentially useful for use as a bioactive cover.